Corporate Social Responsibility (CSR) Communication Strategy of PT Anugrah Argon Medica Bekasi City Branch in Maintaining Company Image - Ilham Kurniawan; Putri Sekar Asih; Nurul Akbar; Wulan Furrie Lenggana (Formosa Journal of Applied Sciences, 2024)
The purpose of this research is to find out and clarify how the Corporate Social Responsibility (CSR) Communication Strategy in Maintaining the Company's Image at PT. Anugrah Argon Medica Bekasi City Branch. An insider at PT acted as the main informant in this research Anugrah Argon Medica Cab. Bekasi city. The research uses qualitative descriptive methods. This research uses a case study methodology. Researchers used data collection strategies, observation, interviews and documentation in addition to conducting in-depth exploration obtained from informants. The role of a good and targeted communication strategy for the company is one of the causes for maintaining a good image for the business. To fulfill CSR objectives at PT. Anugrah Argon Medica Bekasi City Branch in maintaining the company's image. Therefore, persistence, self-control, professionalism and knowledge of communication techniques for delivering and implementing CSR are required.